2010
DOI: 10.5004/dwt.2010.1305
|View full text |Cite
|
Sign up to set email alerts
|

Performance of outside-in pressurized ultrafi ltration in the Qingdao Pilot tests

Abstract: ab s t r ac tA new seawater desalination plant (SWDP) is to be built in Qingdao, China by Befesa Agua, S.A.U. The application of SWDP is to produce drinking water for local residents due to lack of brackish water in north China. Seawater will be treated with membrane technologies to achieve the required water quality. The key process unit operations are ultrafiltration and seawater reverse osmosis. In order to prepare for the detailed design phase and membrane selection, a pilot study was carried out, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Doses are slightly higher with 15-20 mg/l but CEB is slightly less frequent with once every 30-60 minutes. A dose of 500 mg/l once or twice per day has also been reported [86,101,102]. One full-scale Dow plant operated without any CEB [87].…”
Section: Integrated Membrane Systems (Ims)mentioning
confidence: 99%
See 1 more Smart Citation
“…Doses are slightly higher with 15-20 mg/l but CEB is slightly less frequent with once every 30-60 minutes. A dose of 500 mg/l once or twice per day has also been reported [86,101,102]. One full-scale Dow plant operated without any CEB [87].…”
Section: Integrated Membrane Systems (Ims)mentioning
confidence: 99%
“…Chlorine levels in CEB varied between 5-20 mg/l every 15-40 minutes [i.e., every backwash, 98,99,101,119,123], to 20-50 mg/l every 2-6 hours [112,117], up to 100-500 mg/l once or twice per day [98,100,102,107,110,120,121]. These values show a higher upper range than the results of a review carried out by Fritzmann et al [126], who reported chlorine levels of 10-200 mg/l in CEB of UF/MF membranes.…”
Section: Integrated Membrane Systems (Ims)mentioning
confidence: 99%